2023
DOI: 10.32604/phyton.2023.029469
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the SERK Gene Family in Paulownia fortunei and Its Involvement in the Response to Biotic and Abiotic Stresses

Abstract: Somatic embryogenesis receptor-like kinases (SERKs) are receptor-like proteins that contain leucine-rich repeats and are involved in various signaling pathways. This study identified SERK family members in the Paulownia fortunei genome and analyzed their characteristics and expression profiles using bioinformatics methods. We identified 12 SERK genes with relatively conserved gene structures and motifs that were distributed unevenly on eight Paulownia chromosomes. The gene promoters contained various cis-actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Combined with metabolome data, a model of the early defense response to PaWB disease was constructed [59]. Mining the paulownia genome data identified some transcription factor (TF) and functional gene families, such as ARF [77], Aux/IAA [78], BTB [79], bZIP [80], CaM/CML [81], GRAS [82], MADS [83], NCED [84], NLR [85], PP2C [86], SERK [87], SPL [88], TCP [89], UBC E2 [90], and WPR [91], that could be affected by phytoplasma colonization. Expression pattern analyses of transcriptome data and using RT-qPCR further showed that some of these gene family members were differentially expressed among healthy, diseased and MMS-treated diseased in vitro paulownia plantlets, indicating that they may be related to the presence of PaWB phytoplasmas (Table 2).…”
Section: Transcriptional Responsesmentioning
confidence: 99%
“…Combined with metabolome data, a model of the early defense response to PaWB disease was constructed [59]. Mining the paulownia genome data identified some transcription factor (TF) and functional gene families, such as ARF [77], Aux/IAA [78], BTB [79], bZIP [80], CaM/CML [81], GRAS [82], MADS [83], NCED [84], NLR [85], PP2C [86], SERK [87], SPL [88], TCP [89], UBC E2 [90], and WPR [91], that could be affected by phytoplasma colonization. Expression pattern analyses of transcriptome data and using RT-qPCR further showed that some of these gene family members were differentially expressed among healthy, diseased and MMS-treated diseased in vitro paulownia plantlets, indicating that they may be related to the presence of PaWB phytoplasmas (Table 2).…”
Section: Transcriptional Responsesmentioning
confidence: 99%